STUDIES OF SOME PHYSICO-CHEMICAL FACTORS OF TEAK FOREST SOIL FROM KINWAT AREA, NANDED, (MAHARASHTRA) - A. N. KULKARNI; J. V. BALKHANDE; B. D. WAGHMARE; P. U. RATNAKAR; V. S. KANWATE (The Bioscan, 2011)
Kinwat Forest of Nanded district is a dry deciduous type teak forest and about 74568.162 ha. including Mahur forest. Forest soil is enriched by decayed leaves of teak plant and animal dung. Forest is away from industries and anthropogenic activities. The present work was undertaken to study some soil characteristics with reference to season. Surface soil samples were collected from Ambadi and Loni for the study of Colour, pH, Chloride, Alkalinity, Organic carbon, Organic matter, Carbonates and Bicarbonates. Soil slightly brown in colour; pH acidic , Chloride ranged from 0.008% to 0.013%, Alkalinity from 1.5 to 2.6mg/L, Organic carbon from 0.003% to 0.126%, Organic matter from 0.005% to 0.217%, Bicarbonate from 0.091% to 0.134% and Carbonates were nil. The Obtained data is compared with the season to find out seasonal impact.Details about the method, soil characteristics and seasonal impact are discussed in the text.